2013
DOI: 10.5694/mja12.11813
|View full text |Cite
|
Sign up to set email alerts
|

The medical management of missed miscarriage: outcomes from a prospective, single‐centre, Australian cohort

Abstract: Objective: To report the prospective outcomes of medical management of missed miscarriage before 13 weeksˈ gestation from an Australian cohort. Design: Descriptive study of a cohort selected out of a randomised controlled trial. Setting: Outpatient management at a maternity hospital between 1 May 2007 and 28 July 2010. Participants: 264 women requesting medical management of missed miscarriage. Main outcome measures: Number of doses of misoprostol required, unscheduled visits for care, findings at ultrasound f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 54 publications
1
34
1
3
Order By: Relevance
“…Factors that affect outcome for medical treatment for missed miscarriage have been suggested but studies investigating factors influencing success are few and relatively small . High serum‐human chorionic gonadotropin, multiparity, and delaying management after diagnosis have been shown to increase the need for surgical intervention . Women with a present embryo or fetus have been shown to have higher success rates compared with women with anembryonic pregnancies .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that affect outcome for medical treatment for missed miscarriage have been suggested but studies investigating factors influencing success are few and relatively small . High serum‐human chorionic gonadotropin, multiparity, and delaying management after diagnosis have been shown to increase the need for surgical intervention . Women with a present embryo or fetus have been shown to have higher success rates compared with women with anembryonic pregnancies .…”
Section: Introductionmentioning
confidence: 99%
“…8,11,15 High serum-human chorionic gonadotropin, multiparity, and delaying management after diagnosis have been shown to increase the need for surgical intervention. 16,17 Women with a present embryo or fetus have been shown to have higher success rates compared with women with anembryonic pregnancies. 6 If major significant factors influencing success could be determined it would be possible to advise women on optimal management of missed miscarriage.…”
mentioning
confidence: 99%
“…Commonly reported adverse effects with misoprostol were abdominal cramps (20.8%), nausea (12.5%), vaginal bleeding (12.5%), chills (8.33%) and a generalized feeling of warmth (8.33%). The incidence of these is comparable when misoprostol is used for various obstetric indications [15,16]. The comparatively lower incidence of adverse effects associated with estradiol use (mainly nausea in 13% of the patients) was likely a result of its low-dose local administration.…”
Section: Discussionmentioning
confidence: 80%
“…In the study by Alsibiani 26 In our study, chorionic villi were not identified in 56 out of 190 specimens (29.47%) who were subjected for histopathological examination.…”
Section: Vidyasagar V Int J Reprod Contracept Obstet Gynecol 2015 Ocmentioning
confidence: 94%